Pesticide benefits locust predators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
A pesticide that not only kills locusts, but simultaneously benefits one of their natural enemies, has been identified by scientists in South Africa. Normally pesticides kill both the target insects and their predators. But Roger Price and his...